PENGEMBANGAN BAHAN AJAR BERBASIS KEMAMPUAN PEMECAHAN MASALAH PADA MATERI KESEBANGUNAN DAN KEKONGRUENAN - Lia Kurniawati; Eva Musyrifah; Utari Narulita (ALGORITMA: Journal of Mathematics Education, 2022)
AbstractThis study aims to develop teaching materials based on problem-solving abilities in the materials of similarity and congruence at SMP/MTS. Problem solving ability is the ability to solve mathematical problems that are non-routine or procedural as usual which require deeper thinking in solving them. The teaching materials chosen are in the form of student worksheets (LKS). The trial subjects were taken based on nonprobability sampling techniques, specifically purposive sampling, namely 13 students one of the SMP/MTS level schools in Pamulang. The method used in this research is the ADDIE model development research method (Analysis, Design, Development, Implementation, Evaluation). The results showed that the teaching materials developed fell into the very feasible category with a percentage score of 87.11% according to experts consisting of 3 lecturers in the mathematics education department at UIN Syarif Hidayatullah Jakarta and 5 mathematics teachers from several SMP/MTS. The results of the limited trial for students who obtained a percentage score of 80.92% were categorized as feasible by the students. Keywords: Problem Solving Ability, Similarity and Congruence Materials, ADDIE Development Model. AbstrakPenelitian ini bertujuan untuk mengembangkan bahan ajar berbasis kemampuan pemecahan masalah pada Materi Kesebangunan dan Kekongruenan SMP/MTS. Kemampuan pemecahan masalah adalah kemampuan dalam menyelesaikan permasalahan matematika yang bersifat non-rutin atau tidak sesuai prosedural seperti biasa yang dalam menyelesaikannya memerlukan pemikiran yang lebih mendalam. Bahan ajar yang dipilih berupa Lembar Kerja Siswa (LKS). Subjek penelitian diambil berdasarkan teknik nonprobability sampling, tepatnya purposive sampling yaitu 13 orang siswa kelas IX salah satu sekolah tingkat SMP/MTS di Pamulang. Metode yang digunakan dalam penelitian ini adalah metode penelitian pengembangan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan masuk ke dalam kategori sangat layak dengan skor persentase 87,11% menurut para ahli yang terdiri dari 3 orang dosen jurusan pendidikan matematika UIN Syarif Hidayatullah Jakarta dan 5 orang guru matematika yang berasal dari beberapa sekolah tingkat SMP/MTS. Hasil uji coba terbatas kepada siswa memperoleh skor persentase 80,92% dikategorikan layak oleh siswa. Kata kunci: Kemampuan Pemecahan Masalah, Matei Kesebangunan dan Kekongurenan, Model Pengembangan ADDIE.